Gender Differences in Anxiety and Self-Disclosure among University Students Using Social Media - Itsna Labbey Mukarromah; Sigit Hariyadi (Journal of Educational Sciences, 2026)
The increasing intensity of social media use among university students influences not only communication patterns and social interactions but also psychological conditions, particularly anxiety and self-disclosure. This study examined gender differences in anxiety and self-disclosure among university students who use social media. A quantitative causal-comparative design was employed involving 348 active students selected through purposive random sampling. Data were collected using an anxiety scale measuring fear of negative evaluation and social avoidance and distress, as well as a self-disclosure scale based on Jourard’s framework. Descriptive analysis and Chi-square tests were applied. The findings indicated a significant gender difference in anxiety levels, with female students more frequently categorized as having high anxiety. In contrast, male students tended to fall within the low-anxiety category. In contrast, no significant gender differences were found in self-disclosure, with most students demonstrating moderate levels. These results suggest that gender differentiates anxiety intensity in social media use but does not play a central role in determining self-disclosure. Overall, students’ psychological experiences on social media are shaped by social pressures, whereas self-disclosure is influenced more by personal considerations and usage context.